Let the Body’n’Brain Games Begin: Toward Innovative Training Approaches in eSports Athletes - Martin-Niedecken, Anna Lisa; Schättin, Alexandra (Frontiers in Psychology, 2020)
The phenomenon of eSports is omnipresent today. International championships and their competitive athletes thrill millions of spectators who watch eSports athletes and their teams try to improve and outperform each other. In order to achieve the necessary cognitive and physical top form and to counteract general health problems caused by several hours of training in front of the PC or console, eSports athletes need optimal cognitive, physical and mental training. However, a gap exists in eSports specific health management, including prevention of health issues and training of these functions. To contribute to this topic, we present in this mini review possible avenues for holistic training approaches for cognitively, physically and mentally fitter and more powerful eSports athletes based on interdisciplinary findings. Furthermore, we discuss exergames as a motivating and promising complementary training approach for eSports athletes, which simultaneously combines physical and cognitive stimulation and challenges in an attractive gaming environment. Exergames have the high potential to penetrate new applications and thus influence the growing eSports research and development community.